Static and fatigue tests of bimetal Zr-steel made by explosive welding. (May 2017) - Prażmowski, Mariusz; Rozumek, Dariusz; Paul, Henryk
Abstract: The paper presents the test results of the microstructure, mechanical properties and fatigue cracks obtained for zirconium-steel bimetal under cyclic bending. The research was carried out for initial state bonds, i.e. immediately following explosion welding. The results of mechanical and structural investigations of the intermediate layers were presented. Using scanning electron microscopy (SEM) allowed the initial identification of the forming phases. In order to determine changes in the value of strengthening, microhardness tests of both the weld and the joined plates were performed. Specimens of rectangular cross section were fatigue tested. In the tested specimens, the ratio of heights of base and overlaid materials was h1 : h2  = 2.5: 1. In the specimens, the fatigue crack growth was parallel to the applied load. The specimens exhibit the uniform crack growth at both sides of lateral surfaces. Among composite fractures in the zirconium and steel, transcrystalline cracks are dominating. Highlights: The results of mechanical and structural investigations of the intermediate layers were presented. The increase of participation of the remelted layer (RGP) from 0.02 for the 1.1vD to 10.98 for the vD was also observed. Hardness of both joined materials in all their section is higher than hardness of the materials before cladding. Static and fatigue test results in a zirconium-steel bimetal under oscillatory bending. The observed features of the ductile fracture on cross-sections bonded materials and brittle fracture in a remelted layer.